The Transformation of Islamic Boarding Schools in Indonesia: A Shift in Organizational Management and Leadership Patterns - Muis, Rizal Rahmawan; Lili, Indriyani; Arifudin, Iis; Gloria, Ria Yulia; Wiradinata, Djohana Rochanda (Universitas Negeri Surabaya, 2025)
The evolution of Islamic boarding schools (pesantren) in Indonesia signifies a fundamental transformation in their approaches to organizational management and leadership. Historically, the pesantren structure has revolved around the figure of the kyai, who embodies spiritual authority, educational leadership, and managerial control. The kyai’s influence, rooted in personal charisma and moral integrity, has long served as the cornerstone of pesantren governance. In the face of modernization and globalization, however, traditional leadership models have been increasingly challenged by the demand for more systematic, transparent, and participatory management practices. The need to enhance institutional accountability, administrative efficiency, and educational quality has driven many pesantren to adopt modern organizational frameworks while striving to maintain their distinctive spiritual ethos. This study aims to examine the ongoing transformation in organizational structures and leadership patterns of kyai in managing pesantren within the context of contemporary education. Employing a qualitative descriptive methodology, data were collected through in-depth interviews, document analysis, and field observations conducted at several pesantren representing diverse typologies and managerial orientations. The findings reveal a gradual yet notable shift from a purely charismatic and centralized leadership model toward a more collaborative and distributed governance structure. Although the kyai continues to serve as the symbolic and spiritual leader, decision-making processes increasingly involve administrators, teachers, and community stakeholders. Structural reforms include clearer delegation of authority, the formation of specialized management units, and the implementation of modern administrative systems. Despite these managerial innovations, pesantren remain deeply rooted in their spiritual and cultural values, which continue to shape institutional identity and guide organizational behavior. The study concludes that pesantren have successfully harmonized traditional religious leadership principles with contemporary management concepts, thereby reinforcing their relevance and sustainability in the modern educational landscape.